Socio-ecological determinants of dengue preventive practices: a cross-sectional study among wet market traders in a selected district in Perak, Malaysia - Kamaruddin, N. I. K.; Md Said, Salmiah; Kadir Shahar, H.; Lim, P. Y. (Wolters Kluwer - Medknow Publications and Media, 2021)
Objective: To determine the level of dengue prevention practices among wet market traders in a Malaysian district and their associated socio-ecological factors including individual, relationships, community and societal factors. Methods: A cross-sectional study involving 246 wet market traders was conducted in a district in Perak state in northwest Malaysia between September 2018 to June 2019. Participants were selected through stratified sampling from four wet markets in Hilir Perak district. Data on dengue prevention practices and associated socioecological characteristics were collected using a validated interviewbased questionnaire. The data were analyzed using SPSS version 25. Multiple logistic regression was performed to identify socioecological determinants of dengue prevention practices among wet market traders in Hilir Perak District. Results: From the total number of respondents, 78% had high dengue prevention practices. Higher dengue prevention practices were associated with owners of wet market shoplots compared to employed workers (adjusted OR 4.18, 95% CI 1.78, 9.85), high perceived susceptibility (adjusted OR 6.93, 95% CI 3.02, 15.92), high familial support (adjusted OR 3.65, 95% CI 1.25, 10.64), and high perceived dengue prevention and control laws and regulations (adjusted OR 3.24, 95% CI 1.44, 7.32). Conclusions: Dengue prevention practices were associated not only with individual determinants but also with other determinants fromrelationships to societal level which must be considered in planning or evaluating current dengue control programs.